USO DE PIMOBENDAN E BUMETANIDA NO TRATAMENTO DE INSUFICIÊNCIA CARDÍACA DESCOMPENSADA EM CÃO – RELATO DE DOIS CASOS - Müller, Daniel C. d. M.; Basso, Paula C.; Amaral, Bruna P.; Rakoski, Andréia S.; Dutra, Luciana H.; Frazão, Cássia C. (Salão do Conhecimento, 2013)
Resumo